Atomically thin spherical shell-shaped superscatterers based on a Bohr model. (18th November 2015) - Li, Rujiang; Lin, Xiao; Lin, Shisheng; Liu, Xu; Chen, Hongsheng
Abstract: Graphene monolayers can be used for atomically thin three-dimensional shell-shaped superscatterer designs. Due to the excitation of the first-order resonance of transverse magnetic (TM) graphene plasmons, the scattering cross section of the bare subwavelength dielectric particle is enhanced significantly by five orders of magnitude. The superscattering phenomenon can be intuitively understood and interpreted with a Bohr model. In addition, based on the analysis of the Bohr model, it is shown that contrary to the TM case, superscattering is hard to achieve by exciting the resonance of transverse electric (TE) graphene plasmons due to their poor field confinements.